Effect of photic stimuli disturbing overt circadian rhythms on the dorsomedial and ventrolateral SCN rhythmicity - Sumová, Alena; Illnerová, Helena (Brain research, 2005)
To ascertain how photic stimuli disturbing overt circadian rhythms affect the endogenous rhythmicity of the suprachiasmatic nucleus (SCN), rats were subjected to constant light (LL) or to a 9-h light pulse encompassing midnight, and rhythms of abundance of the c-Fos-immunoreactive (c-Fos-ir) and the PER1-immunoreactive (PER1-ir) cells were studied during the first 1-2 cycles following release into LL or darkness (DD) within the whole SCN as well as in its ventrolateral (vl) and the dorsomedial (dm) part. LL seemingly abolished the c-Fos rhythm in the whole SCN, while the rhythm persisted in the vl- and dm-SCN. In the dm-SCN, the rhythm of c-Fos-ir was phase-delayed by about 4 h in LL, whereas the rhythm of PER1-ir was affected just slightly. In the vl-SCN, the rhythm of c-Fos photo-induction might be delayed by 5-6 h as compared with the reported rhythm [A. Sumova and H. Illnerova, Am. J. Physiol. 274 (1998) R857-R863], whereas the PER1 profile appeared to be out of phase with that in DD. After a 9-h light pulse encompassing midnight, the rhythm of PER1-ir in the dm-SCN changed just slightly, whereas the PER1 rhythm in the vl-SCN was abolished and there was just an indication of extension of elevated PER1-ir. Altogether, the data indicate that photic stimuli disturbing circadian rhythms affect more dramatically the vl- than the dm-SCN rhythmicity within the first cycles and that in the dm-SCN shifting of the c-Fos rhythm proceeds more rapidly than that of the Per1 rhythm.
Keywords: cirkadiánní rytmus; protoonkogenní proteiny c-fos; Suprachiasmatic Nucleus; analýza rozptylu; Analysis of Variance; počet buněk; jaderné proteiny; krysa rodu Rattus; Cell Cycle Proteins; zvířata; neurony; Immunohistochemistry; Photic Stimulation; světelná stimulace; imunohistochemie; potkani Wistar; Periodicity; Circadian Rhythm; periodicita; nucleus suprachiasmaticus; Rats, Wistar; Male; Nuclear Proteins; Neurons; proteiny buněčného cyklu; Rats; Animals; mužské pohlaví; Proto-Oncogene Proteins c-fos; cirkadiánní proteiny Period; Cell Count; Period Circadian Proteins